2015
DOI: 10.1007/s00344-015-9496-7
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate Strengthens Wheat Plants Against Root and Crown Rot Pathogen Fusarium culmorum Infection

Abstract: Root and crown rot of wheat, caused by Fusarium culmorum (Fc), is a serious disease worldwide, particularly in Iran. Currently, the mechanisms underlying resistance to Fusarium-caused diseases are still unknown. Methyl jasmonate (MeJA) has been identified as a vital cellular regulator, and the effect of exogenous MeJA application during wheat-Fc interaction has not been studied previously at the molecular level. This study, using realtime quantitative PCR, was carried out to determine the expression of seven h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…S1). Our previous research has reported that exposure of wheat genotypes to MeJA during the later stages of infection beginning at 1 dpi and later promoted resistance, while when applied prior to inoculation or at the time of fungal inoculation, attenuated FCRR resistance (Motallebi et al 2015b). Whereas, present results using MeJA treatment at 6 hai clearly indicate that the induction of defense genes in wheat occurred at the beginning of the necrotrophic stage in a genotype dependent manner.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…S1). Our previous research has reported that exposure of wheat genotypes to MeJA during the later stages of infection beginning at 1 dpi and later promoted resistance, while when applied prior to inoculation or at the time of fungal inoculation, attenuated FCRR resistance (Motallebi et al 2015b). Whereas, present results using MeJA treatment at 6 hai clearly indicate that the induction of defense genes in wheat occurred at the beginning of the necrotrophic stage in a genotype dependent manner.…”
Section: Discussioncontrasting
confidence: 55%
“…Even if there are several studies on wheat-pathogen interaction (Desmond et al 2006;Makandar et al 2010;Beccari et al 2011;Makandar et al 2012;Motallebi et al 2015b), little is known about the contribution of JA derivatives, such as MeJA, to the resistance mechanisms. In the current work, several genes expression has been investigated to better understand the differences between susceptible and tolerant wheat genotypes infected by F. culmorum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In rice, root SA application results in higher leaf concentrations of phytoalexins such as oryzalexins and momilactone A (26). Similarly, exogenous root application of MeJA (methyl jasmonate) induces expression of defense-associated genes, including a 13-lipoxygenase gene (LOX), PR-3, and PR-4 in wheat crowns and reduces crown symptoms of the pathogen Fusarium culmorum (114). Exogenous shoot application of both SA and JA contributes to resistance to clubroot disease caused by the protist Plasmodiophora brassicae in A. thaliana (90).…”
Section: Cross-compartment Effects Of Exogenous Hormone Applicationmentioning
confidence: 99%